NGO perspectives on the challenges and opportunities for real-world evaluation: a qualitative study. Issue 1 (31st December 2022) - Sawadogo-Lewis, Talata; Bryant, Ruth; Roberton, Timothy
ABSTRACT: Background: The move towards robust monitoring and evaluation (M&E) has been increasing in global health, motivated by both an accountability agenda and to increase learning from M&E activities. Many international non-governmental organizations (NGOs) receive funding from one or more large institutional donors. Objective: To understand NGOs' perspective on their own role in terms of accountability to both donors and the populations they serve. Methods: We conducted a series of in-depth interviews with M&E staff in 11 NGOs with projects related to maternal and child health to better understand how M&E is being implemented in these organizations. We then examined the data based on a priori identified themes. Results: We found that despite flexibility from some donors, rigid reporting structures remain a barrier for NGOs to fully communicate the impact of their projects. While NGOs do utilize M&E findings, their use is limited by low staff capacity. The primary audience for the results remains the donor agency, and the primary motivation for M&E remains donor reporting. Reporting remains a burdensome affair, with ongoing limitations around streamlining results for donors. To reduce the burden of reporting for individual projects, the participants in our study suggested placing greater emphasis on process evaluations rather than impact evaluations. Participants also suggested increased data sharing between organizations working in the same regions and making better use of secondary data sources; in both cases to reduce the need for primary data collection. Conclusion: We carried out this work to advance the conversation on how NGOs currently manage their M&E – a conversation which should involve NGOs, donors, local health system actors, and the communities with whom they work. More flexibility from donors, increased use of technology, and more transparency on if and how data is being used would help NGOs with their M&E process.